ACROMEGALY: CURRENT MANAGEMENT AND THE EMERGING ROLE OF ORAL PALTUSOTINE - Justyna Całka,; Monika Kowalska,; Katarzyna Ścibisz,; Dominika Zdobylak,; Karolina Ollik,; Kamil Harenza,; Anita Zięba,; Michał Domin,; Mateusz Taranowicz,; Olga Kowalczyk, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and aim: Acromegaly is a chronic endocrine disorder caused by sustained excess secretion of growth hormone and insulin-like growth factor I, leading to significant morbidity and increased mortality if inadequately treated. Transsphenoidal surgery remains the primary therapeutic approach; however, a substantial proportion of patients fail to achieve durable biochemical remission and require long-term medical therapy. Injectable somatostatin receptor ligands are effective but are associated with treatment burden, variable biochemical responses, and impaired quality of life. The aim of this review was to summarize current management strategies for acromegaly and to evaluate the emerging role of paltusotine, a novel orally administered somatostatin receptor agonist.Materials and Methods: This narrative review was based on a structured analysis of published clinical trials, extension studies, and review articles evaluating the pharmacological properties, clinical efficacy, and safety of paltusotine in patients with acromegaly.Results: Available evidence indicates that paltusotine provides effective suppression of growth hormone secretion and reduction of insulin-like growth factor I levels with once-daily oral administration. Clinical studies demonstrate maintenance of biochemical control in patients previously treated with injectable therapies, as well as efficacy in selected untreated individuals. Paltusotine was generally well tolerated, with predominantly mild gastrointestinal adverse events and elimination of injection-related complications.Conclusions: Paltusotine represents a promising oral alternative to injectable somatostatin receptor ligands, with the potential to reduce treatment burden, improve adherence, and maintain biochemical control. Further long-term and real-world studies are needed to fully define its role in routine clinical practice.